QUALITY OF LIFE AND ITS RELATION TO STRESSORS ELDERLY NURSING HOME REZIDENTS IN LATVIA - Deklava, Liana; Apsite, Monta; Millere, Inga; Fokina, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
There is a lot of talk about global aging in society and, as people start to live longer, the society has to take care about their well- being in old age too. There are developed a series of definitions about life quality and designed a variety of methods for assessing quality of life of different groups of people and society as a whole over the time. At such a group of people belongs also those who lives in a nursing home and for various reasons they are aging in one of the nursing homes in Latvia. A study has been made to examine the correlation between stressors and quality of life of nursing home residents. The study objective was quantification method - survey, using two research instruments - questionnaires and 134 nursing home residents were interviewed. The results show that there are both positive and negative relationship between stressors and indicator of quality of life. Overall, the results after the quality of life index characterize the situation as good, the figure is described as an adequate quality of life for the majority of respondents, but for a part of respondents in several, important areas of life there is needed an improvement.